2017
DOI: 10.18632/oncotarget.18317
|View full text |Cite
|
Sign up to set email alerts
|

Associations between two common single nucleotide polymorphisms (rs2241766 and rs1501299) of ADIPOQ gene and coronary artery disease in type 2 diabetic patients: a systematic review and meta-analysis

Abstract: ADIPOQ gene polymorphisms were indicated to be associated with coronary artery disease (CAD) in diabetic patients, however, published studies reported inconsistent results. We performed this meta-analysis to reach a more accurate estimation of the relationship between two common ADIPOQ genetic polymorphisms (rs2241766 and rs1501299) and CAD risk in diabetic patients. Eligible studies were retrieved by searching PubMed, Embase, Wangfang, VIP database and China National Knowledge Infrastructure databases. Includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Zhang et al reported only the weak protective effect of the rs1501299 variant against CVD in general study subjects [ 50 ]. The meta-analysis by Zhao et al revealed that rs1501299 polymorphism may play a protective role for CAD among patients with T2DM [ 22 ]. In comparison, our results revealed no significant association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al reported only the weak protective effect of the rs1501299 variant against CVD in general study subjects [ 50 ]. The meta-analysis by Zhao et al revealed that rs1501299 polymorphism may play a protective role for CAD among patients with T2DM [ 22 ]. In comparison, our results revealed no significant association.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin is encoded by ADIPOQ which is located in chromosome 3q27 [ 21 ], and adiponectin levels are influenced by single-nucleotide polymorphisms (SNPs) in ADIPOQ [ 22 ]. SNPs in ADIPOQ have been found to be associated with CVD [ 23 , 24 ], diabetes [ 25 , 26 ], stroke [ 27 , 28 ], myocardial infarction [ 29 , 30 ], cancer [ 31 , 32 ], kidney disease [ 33 , 34 ], and even gynecological conditions [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kanu et al [14] enrolled 29 studies and 29 021 subjects, and obtained similar finding as previous meta-analyses [12,13], that is, G allele of the rs266729 polymorphism significantly increased the risk of CAD. Several meta-analyses [15][16][17] demonstrated that T allele of the rs1501299 polymorphism is a protective allele for CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Hou et al [15] enrolled 23 studies and 17 333 subjects, and the result showed that T allele of the rs1501299 polymorphism was significantly associated with reduced risk of CAD in Caucasian population. Zhao et al [16] conducted a meta-analysis in the patients with diabetes mellitus (DM), and found that the CAD risk of the patients with TT genotype of the rs1501299 polymorphism was reduced by about 50 % as compared with that of the G allele carriers. Regarding the rs2241766 polymorphism, Kanu et al [14] conducted a meta-analysis in which 40 studies and 25 548 participants were enrolled and found that the G allele significantly increased the risk of CAD as compared with the T allele, which is consistent with the findings in several other meta-analyses [15,16,18].…”
Section: Introductionmentioning
confidence: 99%
“…e ADIPOQ gene contains a number of SNPs, mostly of unknown functions. Among such SNPs are rs1501299 and rs2241766 that have been shown to be of clinical significance [25][26][27][28]. is includes modulation of disease susceptibility and the clinical outcomes to therapeutic agents [15,26,29,30].…”
Section: Introductionmentioning
confidence: 99%